Evaluation of Risk Factors for Periprosthetic Joint Infection Following Reverse Shoulder Arthroplasty: A Multivariate Analysis Study - ŞAHİN K.; KAYA H. B.; Demirkiran C. B.; ZİROĞLU N.; Koukos C.; UÇAN V.; KAPICIOĞLU M.; Bilsel K. (My University, 2025)
Background/Objectives: Reverse shoulder arthroplasty (RSA) has been widely used for the treatment of shoulder pathologies, particularly rotator cuff tear arthropathy. Currently, it is also increasingly performed for different indications. Like in any arthroplasty procedure, periprosthetic joint infection (PJI) is one of the most concerning complications and may have devastating outcomes. This study aimed to identify risk factors for PJI following RSA. Methods: This retrospective case-control study was conducted with patients who underwent RSA during the study period. Based on PJI occurrence during the follow-up period, patients were divided into two groups: Group I (no infection) and Group II (infection). The relationship between numerous clinical variables and PJI was tested. All variables were initially evaluated through univariate analysis between the two groups, and variables showing significant differences between the two study groups were subjected to multivariate logistic regression analysis to determine independent risk factors. Results: The study included 302 patients, with a mean age of 69.6 +/- 10.1 years and a mean follow-up duration of 59.8 +/- 24.7 months. During the follow-up period, PJI was not detected in 289 patients (95.7%) (Group I), while 13 patients (4.3%) developed PJI (Group II). Univariate analysis revealed a significant association between preoperative C-reactive protein (CRP) value (p = 0.001) and preoperative diabetes history (p = 0.007) with PJI. Multivariate logistic regression analysis, including these two variables, showed that diabetes was an independent risk factor for PJI development (p = 0.01, odds ratio = 4.85). Preoperative CRP elevation was not observed as an independent risk factor. Conclusions: This study demonstrated a significant association between high preoperative CRP levels and diabetes with PJI. Additionally, the presence of diabetes was identified as an independent risk factor for infection, with a 4.85-fold higher risk of PJI development in patients with a history of diabetes.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Tıp Genel & Dahili; Klinik Tıp; Klinik Tıp (Med); Medicine General & Internal; Clinical Medicine; Clinical Medicine (Med); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine